Political Discourse in Iraq after 2003 - J. Nayef, Karim (International Journal of Psychosocial Rehabilitation, 2020)
On the 9th of April 2003, a totally radical change happened in Iraqi society: a change from authoritarian dictatorship to a complete Western kind of democracy. The majority of Iraqis were very eager for that change after long years of poverty, horrible death, wars, and suppression. But the fact that the Iraqi people consists of different nationalities and religions and different doctrines led to the emergence of a variety of intellectual trends and multiple affiliations which have had a great impact on the diversity of Iraqi political discourse. This article attempts to shed light on the political discourse of three political and religious sections that have a great influence in guiding the Iraqi public and then makes a comparison between them. We will address the Shiite side as a model for the speech of Mr. Muqtada al-Sadr, who represents the majority of the poor and uneducated people, and the speech of Mr. Noori al-Maliki, due to the fact that he was elected twice as the Iraqi prime minister. On the Sunni side, we will take the example of the speech of Dr. Adnan al-Dulaimi, who won the majority of Sunni seats in the Iraqi parliament in its first session. From the Kurdish side, we will address the speech of Mr. Massoud Barzani, the president of the Kurdistan region from 2003 to the present time. The article analyzes the vocabularies and the tones of the selected speeches. The sources on which this article is based are television statements, YouTube, and tweets written by politicians on Twitter.